Analysis of Religious Services in Abu Al-Khaseeb City - Yasser Abdul-Ridha , Assist. Lect . Amjad; Khairallah Khalaf , Prof. Dr. Maryam (Basra studies journal, 2026)
Religious factors play a fundamental role in shaping interaction between inhabitants and urban environments, and they have often influenced the emergence and development of many cities. Historically, a close relationship has existed between religious functions and urban growth. Despite the importance of these services, planning efforts related to them have often been below expectations. This study explores the religious services available in Abu Al-Khasib: the land area they occupy, their geographical distribution, and the efficiency of their distribution. It also uncovers any defects in their placement within the city’s residential neighborhoods and examines whether residents feel satisfied with the religious services provided. The study further highlights that religious services in the city played a direct role in its establishment, growth, and the distribution of religious institutions—especially mosques and jama‘ahs—which had a clear and profound influence on the development of other urban functions. The research found that there are mosques and jama‘ahs in the city, and … [the abstract continues].